Pregnancy loss and role of infant HIV status on perinatal mortality among HIV-infected women - Kim Hae-Young; Kasonde Prisca; Mwiya Mwiya; Thea Donald M; Kankasa Chipepo; Sinkala Moses; Aldrovandi Grace; Kuhn Louise (BMC, 2012)
Abstract Background HIV-infected women, particularly those with advanced disease, may have higher rates of pregnancy loss (miscarriage and stillbirth) and neonatal mortality than uninfected women. Here we examine risk factors for these adverse pregnancy outcomes in a cohort of HIV-infected women in Zambia considering the impact of infant HIV status. Methods A total of 1229 HIV-infected pregnant women were enrolled (2001-2004) in Lusaka, Zambia and followed to pregnancy outcome. Live-born infants were tested for HIV by PCR at birth, 1 week and 5 weeks. Obstetric and neonatal data were collected after delivery and the rates of neonatal (<28 days) and early mortality (<70 days) were described using Kaplan-Meier methods. Results The ratio of miscarriage and stillbirth per 100 live-births were 3.1 and 2.6, respectively. Higher maternal plasma viral load (adjusted odds ratio [AOR] for each log10 increase in HIV RNA copies/ml = 1.90; 95% confidence interval [CI] 1.10-3.27) and being symptomatic were associated with an increased risk of stillbirth (AOR = 3.19; 95% CI 1.46-6.97), and decreasing maternal CD4 count by 100 cells/mm3 with an increased risk of miscarriage (OR = 1.25; 95% CI 1.02-1.54). The neonatal mortality rate was 4.3 per 100 increasing to 6.3 by 70 days. Intrauterine HIV infection was not associated with neonatal morality but became associated with mortality through 70 days (adjusted hazard ratio = 2.76; 95% CI 1.25-6.08). Low birth weight and cessation of breastfeeding were significant risk factors for both neonatal and early mortality independent of infant HIV infection. Conclusions More advanced maternal HIV disease was associated with adverse pregnancy outcomes. Excess neonatal mortality in HIV-infected women was not primarily explained by infant HIV infection but was strongly associated with low birth weight and prematurity. Intrauterine HIV infection contributed to mortality as early as 70 days of infant age. Interventions to improve pregnancy outcomes for HIV-infected women are needed to complement necessary therapeutic and prophylactic antiretroviral interventions.